Rationale for Indonesia-EFTA Regional Trade Agreement Formation Linked to GATT 1994's 'Substantially All Trade' - Fachrudin Sembiring (Dialogia Iuridica, 2025)
The increasing number of Regional Trade Agreements (RTAs) worldwide reflects the shift from multilateral to regional trade liberalization, posing challenges to the World Trade Organization (WTO) framework under Article XXIV of GATT 1994. Indonesia’s participation in the Indonesia–EFTA Comprehensive Economic Partnership Agreement (IE-CEPA) raises the question of whether the agreement satisfies the “substantially all trade” requirement and whether it is driven by economic or political rationale. This paper hypothesizes that Indonesia’s formation of the IE-CEPA was predominantly political rather than economic, aiming to strengthen diplomatic relations and strategic positioning in Europe rather than to expand market access. Using a normative legal method supported by trade data analysis. The findings reveal that while Indonesia and EFTA have formally satisfied the legal test of “substantially all trade,” the underlying rationale for Indonesia’s participation is predominantly political rather than economic. The agreement reflects Indonesia’s diplomatic ambition to strengthen its strategic relations with Europe, indicating that compliance with the “substantially all trade” clause serves more as a legal formality than an instrument of genuine trade liberalization.